2020
DOI: 10.1002/ejoc.201901928
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of C3 Alkoxylated Quinoxalin‐2(1H)‐ones through Dehydrogenative C–H/O–H Cross‐Coupling

Abstract: A highly efficient electrochemically dehydrogenative C–H/O–H cross‐coupling between quinoxalin‐2(1H)‐ones and alcohols was developed under mild conditions. Using different types of alcohols as solvent, various 3‐alkoxylated quinoxalin‐2(1H)‐ones were synthesized in a simple undivided cell at room temperature. This novel electrochemical cross‐dehydrogenative coupling approach features broad functional group tolerance, metal‐ and oxidant‐free conditions, and moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…demonstrated that the electrochemical deoxygenative functionalization with alkyl carbazates allowed the C3 alkylation of quinoxalin‐2(1 H )‐ones [22d] . Recently, electrochemical oxidative C3 thiolation, [22e] alkoxylation, [22f] decarboxylative alkylation, [22g] alkylation [22h] and phosphorylation [22i] of quinoxalin‐2(1 H )‐ones were reported by several groups. In 2018, Gooßen revealed that the direct electrochemical C−H cyanation of electron‐rich (hetero)arenes could be achieved by using NaCN as the nucleophilic cyano source [23] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that the electrochemical deoxygenative functionalization with alkyl carbazates allowed the C3 alkylation of quinoxalin‐2(1 H )‐ones [22d] . Recently, electrochemical oxidative C3 thiolation, [22e] alkoxylation, [22f] decarboxylative alkylation, [22g] alkylation [22h] and phosphorylation [22i] of quinoxalin‐2(1 H )‐ones were reported by several groups. In 2018, Gooßen revealed that the direct electrochemical C−H cyanation of electron‐rich (hetero)arenes could be achieved by using NaCN as the nucleophilic cyano source [23] .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above experimental results and previous reports, a plausible mechanism for this electrochemical C−H cyanation is proposed in Scheme 6. Firstly, quinoxalin‐2(1 H )‐one 1 a would undergo a single‐electron transfer (SET) oxidation at the anode to generate the radical cation intermediate A [22a,f] . Subsequently, the intermediate A would be captured by the nucleophilic cyano source TMSCN to deliver radical B [25] .…”
Section: Methodsmentioning
confidence: 99%
“…Jiang et al reported the coupling of quinoxalin-2(1H)-ones with alcohols to afford 3alkoxylated quinoxalin-2(1H)-ones in a simple undivided cell using Pt plate as cathode and graphite rod as an anode and lithium perchlorate as an electrolyte using 5 mA current (Scheme 61). [58] The reaction offered a wide functional group tolerance to afford variously substituted coupled products.…”
Section: Reactions Involving Radical Intermediatesmentioning
confidence: 99%
“…Generally, alcohols participate in the formation of C-O bonds as nucleophiles. In 2020, Li, Yu and co-workers [26] exploited an efficient electrochemical protocol for the synthesis of 3-alkoxylated quinoxalin-2(1H)-ones through dehydrogenative C-H/O-H cross-coupling (Scheme 21). With graphite rod as anode and Pt plate as cathode, different quinoxalin-2(1H)-ones bearing electron-rich and electronpoor substituents reacted smoothly, affording the corresponding products in moderate to good yields under standard conditions.…”
Section: Electrochemical C -H Alkoxylation Of Quinoxalin-2(1h)-onesmentioning
confidence: 99%